Using brefeldin A to disrupt cell wall polysaccharide components in rice and nitric oxide to modify cell wall structure to change aluminum tolerance - Yan, Jianchao; Zhu, Jiandong; Zhou, Jun; Xing, Chenghua; Song, Hongming; Wu, Kun; Cai, Miaozhen (Frontiers in Plant Science, 2022)
The components and structure of cell wall are closely correlated with aluminum (Al) toxicity and tolerance for plants. However, the cell wall assembly and function construction in response to Al is not known. Brefeldin A (BFA), a macrolide, is used to disrupt cell wall polysaccharide components, and nitric oxide (NO), a signal molecule, is used to modify the cell wall structure. Pretreatment with BFA accelerated Al accumulation in root tips and Al-induced inhibition of root growth of two rice genotypes of Nipponbare and Zhefu 802, and significantly decreased the cell wall polysaccharide content including pectin, hemicellulose 1, and hemicellulose 2, indicating that BFA inhibits the biosynthesis of components in the cell wall and makes the root cell wall lose the ability to resist Al. The addition of NO donor (SNP) significantly alleviated the toxic effects of Al on root growth, Al accumulation, and oxidative damage, and decreased the content of pectin polysaccharide and functional groups of hydroxyl, carboxyl, and amino in the cell wall via FTIR analysis, while had no significant effect on hemicellulose 1 and hemicellulose 2 content compared with Al treatment. Furthermore, NO didn't change the inhibition effect of BFA-induced cell wall polysaccharide biosynthesis and root growth. Taken together, BFA disrupts the integrity of cell wall and NO modifies partial cell wall composition and their functional groups, which change the Al tolerance in rice.